PERSIAPAN UNAS SD MELALUI PELAKSANAAN DAN PEMBAHASAN TRY OUT DI DESA SUMOKALI - Dina Merris Maya Sari (STKIP PGRI Sidoarjo, 2018)
National examination is a national-scale evaluation conducted by government as a measuring tool to know the successful of all elements in the education process. But the national examination is often a frightening thing for the students because the society still considers the national examination results as the only measuring tool in the successful of the students. Students also often feel anxious and worried in facing the national examination. The purpose of this activity is to optimize the preparation of students in facing the national examination through various activities in the execution of implementation and discussion of exercise questions (try out). The methods include socialization, implementation and evaluation. From the results obtained, it can be seen that students have a better level of readiness after several times doing exercise questions (try out). It shows that if students often practice doing exercise questions (try out), then students will have a better degree of readiness in facing the national examination.